“FREQUENCY OF HYPOTHYROIDISM IN PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE” (The Research of Medical Science Review, 2025)
Introduction: The prevalence of non-alcoholic fatty liver disease (NAFLD) in adults has been reported to be high, making it the most common cause of chronic liver disease. Metabolic derangements are suggested to be the main cause of NAFLD. The aim of our study was to determine the frequency of hypothyroidism in patients with non-alcoholic fatty liver disease Objective: To determine the frequency of hypothyroidism in patients with non-alcoholic fatty liver disease at a tertiary care Hospital, KarachiSetting: This study was conducted in department of Internal Medicine, Liaquat National Hospital, karachiStudy Design; Cross Sectional studyDuration of study; 6 months from 24th June 2023 to 24th Dec 2023Subject & methods: All patients who fulfilled the inclusion criteria in the department of Department of General Medicine, Liaquat National Hospital, Karachi were included in the study. After taking informed and written consent history was taken, clinical examination was done and serum TSH, free T3 and free T4 levels were checked to reach the outcome i-e hypothyroidism.Result: Total of 149 patients with non-alcoholic fatty liver disease were included. 81 patients (54.4%) were males & 68 patients (45.6%) were females with the mean age of 42.295+9.986 years. Hypothyroidism was noted in 19 (12.8%) patients.Conclusion: In conclusion the frequency of hypothyroidism in patients with non-alcoholic fatty liver disease was not much low, it increases with the decrease in age and increase in BMI & predominant in female gender.